Local politics and contemporary transformations in the Arab world governance beyond the center - Bouziane, Malika 1978-; Harders, Cilja 1968-; Hoffmann, Anja 1984- (Palgrave Macmillan, 2013)
The contributors link innovative analytical concepts and ethnographic in-depth case studies from the Arab world. Based on the debates on politics from below and dynamic concepts of state, all the chapters focus on informal institutions, non-elite actors, and the dynamic and contradictory relationship between state and society